2016
DOI: 10.1128/jcm.03195-15
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Epidemiology and Molecular Resistance Mechanisms of Azithromycin-Resistant Neisseria gonorrhoeae in Canada from 1997 to 2014

Abstract: The emergence of Neisseria gonorrhoeae strains with decreased susceptibility to cephalosporins and azithromycin (AZM) resistance (AZM(r)) represents a public health threat of untreatable gonorrhea infections. Genomic epidemiology through whole-genome sequencing was used to describe the emergence, dissemination, and spread of AZM(r) strains. The genomes of 213 AZM(r) and 23 AZM-susceptible N. gonorrhoeae isolates collected in Canada from 1989 to 2014 were sequenced. Core single nucleotide polymorphism (SNP) phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
137
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 41 publications
7
137
2
Order By: Relevance
“…We also identify interspecies mosaic variants of the efflux pump–encoding mtr locus (n = 29 [10%]), with 5 isolates containing both the mosaic mtr locus and C2611T mutations. Demczuk et al recently found ermB and ermC in 3 Azi RS isolates in Canada [26], but we found neither of these genes. Notably, many of the mtrR variants reported in the literature to result in Azi RS were not highly associated with resistance in this data set.…”
Section: Discussioncontrasting
confidence: 96%
“…We also identify interspecies mosaic variants of the efflux pump–encoding mtr locus (n = 29 [10%]), with 5 isolates containing both the mosaic mtr locus and C2611T mutations. Demczuk et al recently found ermB and ermC in 3 Azi RS isolates in Canada [26], but we found neither of these genes. Notably, many of the mtrR variants reported in the literature to result in Azi RS were not highly associated with resistance in this data set.…”
Section: Discussioncontrasting
confidence: 96%
“…High-level azithromycin resistance (MIC Ն 256 g/ml) is associated with NG-STAR ST-30, ST-36, ST-69, ST-192, ST-202, ST-223, and ST-225, all of which possess the 23S rRNA A2059G mutation of allele 23S-1. Previous molecular studies have shown that these isolates possessed the A2059G mutation in all 4 alleles (36). Although more than a single mutated 23S rRNA gene in the genome is required to confer elevated azithromycin MICs (28,36), the acquisition of a single mutated allele facilitates the rapid acquisition of a full complement of mutated alleles under selective pressures (3,29); therefore, the presence of a single mutation may be considered a precursor to full resistance, especially if inappropriate treatment adds to this selective pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous molecular studies have shown that these isolates possessed the A2059G mutation in all 4 alleles (36). Although more than a single mutated 23S rRNA gene in the genome is required to confer elevated azithromycin MICs (28,36), the acquisition of a single mutated allele facilitates the rapid acquisition of a full complement of mutated alleles under selective pressures (3,29); therefore, the presence of a single mutation may be considered a precursor to full resistance, especially if inappropriate treatment adds to this selective pressure. It is for this reason that NG-STAR records the presence of a mutation, even if present in a single allele, as being sufficient to identify the potential for full azithromycin resistance and to recommend an alternative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Effective STI control will require the political will to prioritise and invest in new 150 rapid molecular methods for predicting AMR (for AMR surveillance but ideally also to inform individualized treatment), [190][191][192] rapid point of care tests for diagnosis of gonorrhoea (ideally with combined prediction of AMR); 190,191 ideal phylogenomics of gonococci and their AMR (also in non-cultured samples); 159,457,[459][460][461][462][463][464] and appropriate models for pharmacokinetics/ pharmacodynamics (urogenital and extragenital sites) and prediction of AMR induction/selection, evolution and biological fitness. -Data are for principal diagnosis, recorded using the ICD-9-CM from 1993-94 to 1997-98, and recording using the ICD-10-AM (Australian modification) from 1998-99.…”
mentioning
confidence: 99%